Orthogonal Generalized \((σ, τ)\)-Derivations on Semiprime \(Γ\)-Semirings - Murty, V. S. V. Krishna; Reddy, C. Jaya Subba; Haseena, Sk. (Communications in Mathematics and Applications, 2025)
In this study, we regard \(M\) as a semiprime \(Γ\)-semiring and introduce the notion of orthogonal \((σ,τ)\)-derivations within such structures. We explore various characterizations of semiprime \(Γ\)-semirings and determine the conditions under which two \((σ,τ)\)-derivations are orthogonal.